Impact of left-ventricular end-diastolic pressure as a predictor of periprocedural hemodynamic deterioration in patients undergoing Impella supported high-risk percutaneous coronary interventions. (February 2020) - Al-Rashid, Fadi; Mahabadi, Amir A.; Johannsen, Laura; Soldat, Julian; Dykun, Iryna; Jánosi, Rolf Alexander; Totzeck, Matthias; Rassaf, Tienush
Abstract: Background: An increasing number of high-risk percutaneous coronary interventions (PCI) are performed with mechanical circulatory support (MCS) to minimize the risk of periprocedural hemodynamic compromise. Prior studies have demonstrated that an elevated left-ventricular end-diastolic pressure (LVEDP) is associated with worse outcome after acute myocardial infarction or cardiac surgery. Although LVEDP is frequently measured, little is known about the usefulness for predicting periprocedural hemodynamic deterioration in high-risk PCI. The objective of this study is to assess the impact of preprocedural measured LVEDP in non-shock patients undergoing high-risk PCI with MCS on periprocedural hemodynamic deterioration. Methods and Results: We reviewed the PCI protocol and the Automated Impella Controller in a consecutive series of 64 patients (mean age 73 years, 80% male), who underwent high-risk PCI with Impella MCS (period 01/2017–12/2018). LVEDP (17 ± 8 mm Hg) was measured in all cases before Impella insertion and start of PCI. Periprocedural hemodynamic deterioration was defined as: systolic blood pressure (SBP) drop (decrease ≥20 mm Hg or ≤90 mm Hg), or transient loss of arterial pressure pulsatility. Hemodynamic deterioration occurred in 33% (n = 21) of all patients but did not lead to a hemodynamic compromise due to the Impella support. Regression analysis of LVEDP for periprocedural hemodynamic deterioration or in-hospital major adverse cardiac and cerebrovascular events (MACCE) showed no significant results. Conclusion: LVEDP was not associated with periprocedural hemodynamic deterioration or a higher rate of in-hospital MACCE. Our data propose that LVEDP may not be used as a risk stratification variable for MCS usage in non-shock patients undergoing high-risk PCI.